2000
DOI: 10.1021/ja0010195
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Word DNA Computing on Surfaces

Abstract: The enzymatic manipulation of DNA molecules immobilized on a surface that each contain linked, multiple "DNA words" is demonstrated, with applications to DNA computing. A new DESTROY operation to selectively remove unmarked DNA strands from surfaces, consisting of polymerase extension followed by restriction enzyme cleavage, has been developed for multiple-word DNA computing. DNA polymerase is used to extend DNA primers hybridized to DNA strands that are covalently attached to a chemically modified gold thin f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…The side-access effect reported in this study has not been hitherto described, although other investigations demonstrated enzymatic reactions on surface-bound DNA molecules 6,[21][22][23][38][39][40][41][42][43][44] . These studies used either longer dsDNA molecules 23,40 or molecules provided with significantly less-rigid surface linkers and/ or different chemical strategies for DNA self-assembly 6,23,39,41 .…”
Section: Discussionmentioning
confidence: 45%
See 2 more Smart Citations
“…The side-access effect reported in this study has not been hitherto described, although other investigations demonstrated enzymatic reactions on surface-bound DNA molecules 6,[21][22][23][38][39][40][41][42][43][44] . These studies used either longer dsDNA molecules 23,40 or molecules provided with significantly less-rigid surface linkers and/ or different chemical strategies for DNA self-assembly 6,23,39,41 .…”
Section: Discussionmentioning
confidence: 45%
“…Several studies involved ligation enzymes 42,43 , the reactions of which occurred on DNA-binding sites that are readily available on the topmost interface of the matrices. In contrast, Corn 39 , and Daube and co-workers 40 used restriction enzymes and dsDNA densities close to our experimental conditions, and their results Figure 4, relative to the DpnII reaction, for consensus (solid blue squares) and control (open red circles) dsDnA matrices. Data are means ± s.d.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…While Adleman's techniques were based on selecting one molecule representing a solution from the midst of many that represented non-solutions, Landweber and co-workers [59] devised methods to create all possible solutions of a problem in the form of RNA-DNA hybrids, and then exhaustively eliminate the sequences that did not satisfy the problem's constraints. This approach was used to solve a combinatorial chess problem using a 10-bit DNA memory strand [60,61]. A similar approach was developed, based on inactivating, rather than digesting the non-candidate solutions at the University of Leiden [47].…”
Section: Dna Strands and Word Designmentioning
confidence: 99%
“…A similar approach was developed, based on inactivating, rather than digesting the non-candidate solutions at the University of Leiden [47]. Chemists at the University of Wisconsin developed a computation format and biological steps based on surface-immobilized oligodeoxynucleotides, high-affinity non-covalent hybridization with PNAs, and fluorescence readout [61]. Considerable efforts have been made to define information content and operations in DNA and other biomolecules according to concepts of mathematics, computer science, and linguistics [34,62].…”
Section: Dna Strands and Word Designmentioning
confidence: 99%